2020
DOI: 10.1177/0309364620956866
|View full text |Cite
|
Sign up to set email alerts
|

Finger orthoses for management of joint hypermobility disorders: Relative effects on hand function and cognitive load

Abstract: Background: Joint hypermobility refers to joints that move beyond their normal limits. Individuals with hypermobility of the fingers experience difficulties in activities of daily living. Finger orthoses are available for managing hypermobility of the fingers, but their effectiveness has received little attention in scholarly literature. Objectives: To determine if use of custom fit finger orthoses leads to improvements in time needed to perform standardised hand function tests, and attentional demand required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…In a small clinical study of the use of finger orthosis for joint hypermobility, results suggested improved function and some evidence of minimized cognitive demand. 48 Compressive clothing, abdominal binders, and sequential compression devices can be worn to provide support or increase circulation. 49,50 Bracing can assist in retaining muscle tone and increase proprioception of affected joints.…”
Section: Modalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a small clinical study of the use of finger orthosis for joint hypermobility, results suggested improved function and some evidence of minimized cognitive demand. 48 Compressive clothing, abdominal binders, and sequential compression devices can be worn to provide support or increase circulation. 49,50 Bracing can assist in retaining muscle tone and increase proprioception of affected joints.…”
Section: Modalitiesmentioning
confidence: 99%
“…Patients with SJH often use foot, finger, and/or oral orthosis (shoe inserts, finger splints, and bite splints). In a small clinical study of the use of finger orthosis for joint hypermobility, results suggested improved function and some evidence of minimized cognitive demand 48…”
Section: Modalitiesmentioning
confidence: 99%
“…Custom-fit finger orthoses can significantly reduce the time to perform functional hand tests [42 ▪▪ ] by providing joint stability and facilitating proprioception.…”
Section: Handmentioning
confidence: 99%
“…Joint hypermobility is defined as movement of the joint beyond the normal range of motion [1,2]. Several causes contribute to its etiopathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Several causes contribute to its etiopathogenesis. One of the primary reasons is attributed to abnormalities in collagen, a protein responsible for the flexibility and strength of joints, ligaments, and tendons [1,3]. Collagen dysfunction can arise from genetic mutations affecting the genes responsible for the structure, composition, or function of connective tissues [3,4].…”
Section: Introductionmentioning
confidence: 99%